Jump from the sky - Murray, W.; Aitchison, Martin (Ladybird London, 2009)
Uses the most frequently met words in the English language as a starting point for learning to read successfully and confidently. This book introduces 109 words, including 'sometimes', 'interesting', 'jumping' and 'balloon'.